A computational mechanistic investigation into the reduction of Pt(iv) prodrugs with two axial chlorides by biological reductants. Issue 8 (12th January 2017) - Ejehi, Zeinab; Ariafard, Alireza
Abstract : The reduction of the Pt(iv ) prodrugs with two axial chlorido ligands by biological reductants does not always proceed via the chloride-bridge inner-sphere mechanism. Abstract : It is widely reported that the Pt(iv ) prodrugs with two axial chlorido ligands are reduced by biological reductants via a chloride-bridged inner-sphere mechanism. By contrast, in this contribution, we demonstrate that although this approach might be true for the reductants with sulphur donors, the reduction by ascorbates preferentially occurs via an outer sphere mechanism.